Early human foraging paleoecology in the highlands of Potosí, Bolivia - José M. Capriles; Juan Albarracin-Jordan; Sergio Calla Maldonado; Claudia Rivera Casanovas (Quaternary Environments and Humans)
For centuries the Cerro Rico of Potosí in the South American Andes has been known as the richest silver mine in the world but also as a notoriously challenging place for human habitation due to its extreme elevation. Nevertheless, little is known about the temporal depth and socioecological dynamics associated with the initial occupation of this region. In this paper, we present an archaeological and paleoecological assessment of the earliest human peopling of Potosí and the eastern south-central Andes. Systematic surveys in two neighboring regions complemented by test excavations, artifact analysis, and radiocarbon dating revealed evidence of foraging occupations dating to the Early Holocene as well as by agropastoralist communities during the Late Holocene. Local paleoenvironmental records suggest that periods of increased humidity might have fostered ecological productivity that incentivized settlement in this high elevation setting. The nature of the occupations and associated technological organization is consistent with findings from sites elsewhere in the arid Andes.